Identification and Ranking of Clinical Compounds with Activity Against Log-phase Growing Uropathogenic Escherichia coli - Niu, Hongxia; Yee, Rebecca; Cui, Peng; Zhang, Shuo; Tian, Lili; Shi, Wanliang; Sullivan, David; Zhu, Bingdong; Zhang, Wenhong; Zhang, Ying (Current Drug Discovery Technologies, 2020)
Background: Uropathogenic Escherichia coli (UPEC) is a major cause of Urinary Tract Infections (UTIs). Due to increasing antibiotic-resistance among UPEC bacteria, new treatment options for UTIs are urgently needed. Objective: To identify new agents targeting growing bacteria that may be used for the treatment of antibiotic-resistant UTIs. Methods: We screened a clinical compound library consisting of 1,524 compounds using a high throughput 96-well plate assay and ranked the activities of the selected agents according to their MICs against the UPEC strain UTI89. Results: We identified 33 antibiotics which were active against log-phase clinical UPEC strain UTI89. Among the selected antibiotics, there were 12 fluoroquinolone antibiotics (tosufloxacin, levofloxacin, sparfloxacin, clinafloxacin, pazufloxacin, gatifloxacin, enrofloxacin, lomefloxacin, norfloxacin, fleroxacin, flumequine, ciprofloxacin), 15 beta-lactam or cephalosporin antibiotics (cefmenoxime, cefotaxime, ceftizoxime, cefotiam, cefdinir, cefoperazone, cefpiramide, cefamandole, cefixime, ceftibuten, cefmetazole, cephalosporin C, aztreonam, piperacillintazobactam, mezlocillin), 3 tetracycline antibiotics (meclocycline, doxycycline, tetracycline), 2 membrane-acting agents (colistin and clofoctol), and 1 protein synthesis inhibitor (amikacin). Among them, the top 7 hits were colistin, tosufloxacin, levofloxacin, sparfloxacin, clinafloxacin, cefmenoxime and pazufloxacin, where clinafloxacin and pazufloxacin were the newly identified agents active against UPEC strain UTI89. We validated the key results obtained with UTI89 on two other UTI strains CFT073 and KTE181 and found that they all had comparable MICs for fluoroquinolones while CFT073 and KTE181 were more susceptible to cephalosporin antibiotics and tetracycline antibiotics but were less susceptible to colistin than UTI89. Conclusion: Our findings provide possible effective drug candidates for the more effective treatment of antibiotic-resistant UTIs.
Keywords: uropathogenic Escherichia coli